Pharmacological Properties Of Medinilla Speciosa With Potential Relevance To Oral Health: A Scoping Review - Arin Oktaviani Suningdyastiningrum; Fatika Puteri Rosyi Prabowo; Agam Ferry Erwana (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
ABSTRACT Background: Oral health is sustained under the control of a dynamic balance between oral microorganisms, host immunity, and oral tissue. Loss of this balance leads to microbial dysbiosis and inflammation associated with many oral diseases. Multitarget agents such as herbal medicine are therefore being increasingly explored, as conventional medicine can lead to some side effects. Medinilla speciosa (Parijoto), an endemic Indonesian medicinal plant, has been reported to possess diverse pharmacological activities. However, its relevance to oral health has not been systematically synthesized.Method: A scoping review was carried out using PubMed, ScienceDirect, Google Scholar, and Semantic Scholar using the search keyword: “Medinilla speciosa” AND (antibacterial OR antioxidant OR anti-inflammatory). The pharmacological activity of Medinilla speciosa was recorded in studies.Result: A total of 253 papers were found 6 papers were selected after rigorous selection process based on the PRISMA scoping review technique. Those studies shows the antibacterial impact on pathogenic bacteria, antioxidant properties, immunomodulation, anti-inflammation. Additionally, although no research has examined the impact of these extracts on oral tissues or models of oral diseases, their pharmacological properties are intriguing in terms of their local control of bacteria, modulation of inflammation, oxidative stress reduction, and tissue repair.Conclusion: Current evidence suggests that Medinilla speciosa exhibits multitarget pharmacological activities with potential relevance to oral health. However, oral-specific experimental and clinical studies are needed for the further validation of its application in dentistry and oral medicine.